KESALAHAN KOMUNIKASI MATEMATIS (TERTULIS) SISWA KETIKA MEMAHAMI SOAL CERITA - Mohammad Archi Maulyda; Vivi Rachmatul Hidayati; Muhammad Erfan; Umar Umar; Deni Sutisna (Universitas Muhammadiyah Semarang, 2020)
Communication is an important ability for every human. Communication in this article is focused on written mathematical communication. This study aims to describe students’ errors in written mathematical communication at SMPN 1 Tembelang, Jombang class VIII F in solving word problems. The type of study is a qualitative descriptive study. The results of the study indicate that (1) there are still many students who are unable to communicate the results of their work properly. (2) The most mathematical error in mathematical communication is couldn’t illustrate the word problems into mathematics equations. (3) It was found that students communicated their answer incoherently (unsystematic and incomplete).